1999
DOI: 10.1093/rheumatology/38.8.721
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between β2-glycoprotein I valine/leucine247 polymorphism and anti-β2-glycoprotein I antibodies in patients with primary antiphospholipid syndrome

Abstract: Anti-beta2GPI antibodies were present in 28 of 57 primary APS patients (49%) and in 19 of 31 secondary APS patients (61%). The allele containing valine247 was significantly more frequent in primary APS patients with anti-beta2GPI antibodies than in controls (OR = 2.51, 95%, CI 1.03-6.13, P = 0.0396) or in primary APS patients without anti-beta2GPI antibodies (OR = 2.92, 95% CI 1.16-7.39, P = 0.0204). This tendency was not found in the secondary APS group. In conclusion, the beta2GPI polymorphism, valine/leucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1
3

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 16 publications
6
40
1
3
Order By: Relevance
“…24 Similarly, positivity for anti-2gp1 is aVected by racial factors, HLA, 24 and polymorphisms in the 2gp1 gene itself. 25 We are unable to draw conclusions on this possibility from the data shown here.…”
Section: Discussionmentioning
confidence: 61%
“…24 Similarly, positivity for anti-2gp1 is aVected by racial factors, HLA, 24 and polymorphisms in the 2gp1 gene itself. 25 We are unable to draw conclusions on this possibility from the data shown here.…”
Section: Discussionmentioning
confidence: 61%
“…Todos os pacientes MB com FTE apresentaram heterozigose ou homozigose (Val/Val), corroborando estudos que atribuem FTE e SAF ao polimorfismo Val247Leu. 13,24,25 Alguns estudos têm relacionado a presença desse polimorfismo com AAF em pacientes com SAF, porém os resultados são controversos. Paloma et al [24][25][26][27] Na hanseníase MB, há descrição da presença de AAF, porém a ocorrência da associação com SAF é rara.…”
Section: Discussionunclassified
“…13 A interferência de AAF na interação fisiológica da β 2 GPI com fatores de coagulação constitui possível mecanismo patogêni-co para a ocorrência de trombose na SAF.…”
unclassified
“…Using domain-deletion mutants of the protein, Iverson et al found that most anti-β2GPI antibodies reacted with domain I [27] There are several studies suggesting there is a clinical correlation between anti domain I anti-β2-GPI and clinical symptoms, both thrombosis and, interestingly, pregnancy morbidity [28] β2-GPI can be found in plasma in the closed circular configuration. This structure changes after interaction with anionic phospholipids (cardiolipin, apoptotic cells surfaces) to become an open linear configuration that exposes the previously hidden domain I epitope [29] and allows interaction with antibodies (Fig. 1).…”
Section: Considering Possible Mechanismsmentioning
confidence: 99%